Assessment of Serum Electrolyte in Hypothyroid Patients Attending Chitwan Medical College (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: Hypothyroidism is a clinical condition resulting from inadequate synthesis of the thyroid hormones. Thyroid hormone has an influence on renal hemodynamics, glomerular filtration, as well as the renin angiotensin aldosterone system and renal electrolyte handling. The aim of present study was to find out the serum concentration of electrolytes sodium and potassium in hypothyroid patients attending a tertiary care hospital. MATERIALS AND METHODS: A hospital-based descriptive cross-sectional study was conducted from 24th July 2019 to November 30th 2019 at Chitwan Medical College Teaching Hospital. A venous blood sample was collected and T3, T4 and TSH levels were measured by using chemiluminescence technology. Sodium and potassium levels in blood were investigated by ion selective electrode (ISE) method. Data were analyzed using IBM SPSS 21 software. RESULTS: In our study parameters (T3, T4 & TSH and Na+) were significant (P